Antibacterial Efficacy of Cinnamon Essential Oil Compared to Standard Antibiotics on Diabetic Foot Ulcer Isolates at Tertiary Care Units Karachi, Pakistan: Antibacterial Efficacy of Cinnamon Essential Oil Compared to Standard Antibiotics on Diabetic Foot Ulcer Isolates at Tertiary Care Units Karachi, Pakistan - Ullah, Ubaid; Rahman, Sameen Adib; Perveen, Kahkashan; Zafar, Benish; Khan, Ayaz; Ahmad, Ashfaq (Pakistan Journal of Health Sciences, 2025)
Lower limb complications associated with Type Ⅱ Diabetes have become a serious public health issue in today's world. Diabetic patients with ulcers commonly experience infection due to Gram-positive, Gram-negative bacteria, as well as some anaerobes. Objectives: To investigate the antibacterial activity of Cinnamon essential oil on microbial isolates from diabetic foot ulcer. Methods: An experimental investigation was carried out on diabetic patients suffering from foot ulcers. A total of 115 pus swab samples from diabetic foot ulcer patients were acquired, who were recruited and processed at Baqai Institute of Diabetology and Endocrinology. Antibiotic sensitivity testing was performed by the Kirby agar Disc diffusion method. Antibacterial activity of cinnamon essential oil was checked by the Kirby agar well diffusion method. Results: Out of 115 samples, 138 bacteria were isolated. 80% of samples were mono-microbial and 20% were poly-microbial. Pseudomonas Aeruginosa was the most frequently encountered bacterium, followed by E. Coli, S. Aureus, Klebsiella Pneumonae, Proteus Mirabilis, Enterococcus species, Coagulase-negative Staphylococcus Species, and Proteus Vulgaris. All the isolated bacteria showed different resistance patterns against commercially available antibiotics. Cinnamon essential oil showed antibacterial activity against all isolated bacteria. Conclusions: The study demonstrated a high bacterial isolation rate from diabetic foot ulcer. Antibiotic resistance varied among bacterial isolates, highlighting the challenge of treating bacterial infections. Cinnamon essential oil exhibited strong antibacterial activity against all isolated bacteria, suggesting its potency of being used as an alternative antimicrobial agent.